Two Suns? Data, Algorithms, Spaces and Techno Feudalism - Cleave, Peter (Te Kaharoa, 2021)
A main thread in the Two Suns? series might be summed up as follows. There are several spaces or forms of space involved; territorial space, outer space, cyberspace and living space, And there is data to be found and owned in each of these spaces. That data may be processed using algorithms in each space and across all spaces. With such a thread in mind one argument in the Two Suns? series so far and going forward is as Data, Algorithms, Spaces, and Techno Feudalism follows; we should treat Big Tech as an incipient state with its own entry and exit points and its own infrastructure rather than constantly framing discussion in terms of a nation-state like the USA. The latter may have been and may still be a host for the Algorithmic State but this is not necessarily ongoing. Furthermore there is a range of nation states from the strong to the barely formed ranging through, say the examples of the USA, Australia and Myanmar and a varying use and influence of the algorithm within these nation states.